DFT Study on the Compatibility Between Bentonite Clay Mineral and Hydration Products With the Polycarboxylate Water Reducer in the Cement Hydration Process - Teng, Huang; He, Zhihao; Meiben, Gao; Zhang, Jiaxing (Frontiers in Earth Science, 2022)
As one of the most used grouting material, cement has the characteristics of low price and wide resource of raw material. With the research and application of the cement admixture going in deep, the compatibility between different water-reducing agents and the clay has become one of the critical factors that affect the cement hydration process. Due to the adsorption of clay on the cement additives, the dispersion efficiency of the water reducer will be reduced, also the strength and impermeability of hydration products will be adversely affected. This paper studies the adsorption characteristics of different PCE superplasticizers on bentonite clay minerals and the hydration products using molecular simulation technique. Results showed that there is competitive adsorption between the clay and hydration products when the admixture participates in the hydration reaction, the additives are likely to adsorb on the CH rather that the clay minerals, while the adsorption energy of the hydration product C-S-H is the highest, thus the preferential adsorption order and compatibility between clay minerals and hydration products on the admixtures could also be obtained. PDOS (partial density of states) analysis conclude that some new characteristic peaks and rearrangement of the bonding orbitals may appear after the adsorption, with the peak value of the minerals higher than that of jennite, which is also consistent with the adsorption energy. This study aims to reveal the interaction mechanism and compatibility between the hydration product and the clay minerals, hoping to fully utilize the advantages both the clay minerals and admixtures in the cement hydration process.